Pormenor e dissipação: o Brasil de Cornélio Penna - Rufinoni, Simone Rossinetti (Teresa, 2015)
The article analyzes some of the novel features of Fronteira by Cornélio Penna – traces of introspective prose, the space of the house, the use of detail, eroticism and the presence of the hazy atmosphere, among others – linking them to an aesthetic apprehension of the decadence of the patriarchal society, in the sense of a possible reading country